Diagnosis Penyakit pada Anjing Menggunakan Metode Promethee - Aditya Purwa Pangestu; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dogs are one of the animals that are often found as pets. The interaction between humans and dogs has many health benefits such as helping reduce stress and making their owners have a more active lifestyle. However, the health of the pet itself must be considered. Dogs that are at risk of developing a disease have the effect of being able to transmit it to other pets or even humans, the condition becomes a little difficult if the new owner realizes that his dog is in an unhealthy condition outside working hours. The limited number of veterinary clinics that can handle patients outside of working hours makes dog owners must be able to provide early treatment immediately. To deal with the problems that arise, a system is needed to help diagnose dog disease by utilizing the Promethee method to help dog owners to detect early dog ​​diseases so that early treatment can be carried out immediately. The system is implemented using the Java programming language. There are 10 types of diseases with symptoms as many as 46. Based on the accuracy testing carried out, the average maximum accuracy is 98%.